Mini review of carbon based additive in machining lubricant - K., Jun Li; Radhiyah, Abd Aziz (Penerbit UMP, 2020)
Milling process is a major machining process used in various type of industries. This process is used to manufacture components such as impellers and structural parts in aerospace industry. Several problems can be arising during the machining operation because 99% of work done produces heat to the chip, the tool and also the workpiece . The temperature of the tool may rise up to 1000oCand this could lead to accelerate the tool wear rate and also the finishing of the surface of the workpiece. In order toimprovise this phenomenon, various type of cutting fluid is used in milling operation to use to reduce the temperature of the workpiece. In general, the fluids are used when cutting the workpiece to lower the heat generated at the interface of the tool chip and also the friction on the workpiece. There are four main types of cutting fluid when commonly found in the market which is straight oils, synthetic fluids, soluble oils and the semi-synthetic fluids. This paper is reviewing on the additive for lubricant and their tribology properties